Evaluasi Manajemen Pengelolaan dan Pemasaran Sarana Prasarana pada Bisnis Olahraga Komplek Pusaka Arena Sukorejo Kendal - Safarudin, Safarudin; Sulaiman, Sulaiman; Priyono, Bambang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This research aims to determine and evaluate the management and marketing of infrastructure in the sports business at the Sukarejo Kendal arena heritage complex. The research approach used is a quantitative method with a descriptive approach. The research design chosen was a cross-sectional survey. Data collection techniques were observation, documentation, and interviews with 15 sources. Data validity techniques use triangulation, data analysis techniques use data reduction and data presentation as conclusions. The research results explain that the CIPP evaluation at the Pusaka Arena Complex went well. In conclusion, the heritage complex's context, input, process, and product aspects are outstanding. Keywords: Evaluation, management, marketing